YES PLEASE, SPOT! - Pitts,Sorrel (c)
Say "Yes, please!" with Spot. Ladybird Readers is a graded reading series of traditional tales, popular characters, modern stories, and non-fiction, written for young learners of English as a foreign or second language. Beautifully illustrated and carefully written, the series combines the best of Ladybird content with the structured language progression that will help children develop their reading, writing, speaking, listening and critical thinking skills. The six levels of Readers and Activity Books follow the CEFR framework and include language activities that provide preparation for the Cambridge English: Young Learners (YLE) exams. Yes please, Spot!, a Beginner Reader, introduces children to their very first conversational phrases.